Experimental and modeling study of the stress-dependent permeability of a single fracture in shale under high effective stress. (1st December 2019) - Zhou, Jian; Zhang, Luqing; Li, Xiao; Pan, Zhejun
Highlights: Permeability tests were performed on fractured shale with high confining pressure. The permeability of the fractured samples decreases sharply with effective stress. A stress-dependent fracture permeability model was derived and validated. Shale fracture compressibility is strongly stress dependent. Abstract: It is of great importance to investigate the change in the permeability of stimulated shale gas reservoirs under high effective stress because the depths of producing shale gas reservoirs in China have gradually exceeded 3500 m. In this study, a series of permeability measurements were performed on two fractured Longmaxi shale samples under confining pressures from 5 to 80 MPa. Experimental results show that the measured apparent permeability of the fractured samples sharply decreases with effective stress. The intrinsic permeability of fractured shale decreases with increasing effective stress, and the Klinkenberg constant is almost invariable. Then, a stress-dependent fracture permeability model was derived based on the fracture compressibility models. The modeling results indicate that the permeability model derived in this study can accurately describe the experimental data, with errors of 5.63% and 2.24% for samples I and II, respectively. A comparison of the modeling results using this model to those using permeability models available in the literature indicates that the model derived in this study is preferable, especially for a broad effective stress range. Moreover, the average compressibility of fractured Longmaxi shale decreases from 0.077 to 0.014 MPa −1 with effective stress increasing from 4.13 to 79.65 MPa, showing that fracture compressibility is strongly stress-dependent. The results in this paper will be important for the prediction of permeability change and gas production behavior for the development of deep shale gas.